The Relationship of Firm Value and Profitability With ESG Disclosures in Property and Real Estate Companies in Indonesia Stock Exchange - Renhard Panjaitan; Yunieta Anny Nainggolan (Research Synergy Foundation, 2025)
This research aims to investigate the relationship between firm value and profitability on Environmental, Social, and Governance (ESG) disclosure on property and real estate companies listed on the Indonesian Stock Exchange. The sample used was 32 samples with 32 observations using the purposive sampling technique. The data used is secondary data, with the data collection method using content analysis. The analysis technique used is linear regression analysis. The dependent variable is ESG Score; the independent variables are two performance indicators (Tobin’s Q and Return on Assets); the control variables are firm size and financial leverage. standards. A one-year lag consideration is used on ESG disclosure. The results of the research indicate (1) firm value and profitability, as measured by Tobin's Q and Return on Assets, respectively, simultaneously have a significant and positive relationship on the level of ESG disclosure; (2) firm value, as measured by Tobin's Q, does not have a significant relationship on the level of ESG disclosure. (3) profitability, as measured by Return on Assets, has a significant and positive relationship with the level of ESG disclosure. Research findings are beneficial for investors, fund managers, policymakers, and property and real estate companies. The author further provides suggestions to executives on ESG investment and practices to gain the benefits of such investments.